2021
DOI: 10.1111/raq.12570
|View full text |Cite
|
Sign up to set email alerts
|

Commensal bacteria‐immunity crosstalk shapes mucosal homeostasis in teleost fish

Abstract: Aquaculture is a fast-growing and rapidly expanding industry worldwide, which currently represents an important food source for the human population, providing more than 20% of the world's animal protein requirements and maintaining an accelerated growth rate of 18% per year. 1,2 During the past decades, aquaculture systems have gradually shifted from extensive to intensive, with stocking densities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 261 publications
(531 reference statements)
5
39
0
Order By: Relevance
“…To prevent the microbiota that populates the mucus from gaining access into the mucosal epithelium, sIgA acts through an immune exclusion mechanism in mucosal surfaces by coating different commensal bacteria 40 , 41 . Here we determined that sIgT is the main Ig class that coats the SB microbiota, while a smaller portion of the bacteria was coated by sIgM and sIgD as has been shown also for other trout MALTs 22 , 42 . Interestingly, we found that the SB represented the trout MALT with the lowest concentration of bacteria, a feature that resembles that of the lung.…”
Section: Discussionsupporting
confidence: 67%
“…To prevent the microbiota that populates the mucus from gaining access into the mucosal epithelium, sIgA acts through an immune exclusion mechanism in mucosal surfaces by coating different commensal bacteria 40 , 41 . Here we determined that sIgT is the main Ig class that coats the SB microbiota, while a smaller portion of the bacteria was coated by sIgM and sIgD as has been shown also for other trout MALTs 22 , 42 . Interestingly, we found that the SB represented the trout MALT with the lowest concentration of bacteria, a feature that resembles that of the lung.…”
Section: Discussionsupporting
confidence: 67%
“…Synergistic and competitive interactions between host immunity and microbiota emerged in both primitive and modern vertebrates to maintain mucosal tissue surface homeostasis and respond to disease ( 2 , 4 ). The upper respiratory tract of mammals is populated with a vast range of commensals and potentially pathogenic bacteria, which occupy different ecological niches and form a complex microbial community.…”
Section: Discussionmentioning
confidence: 99%
“…The mucosa of vertebrates is a particularly dynamic environment in which trillions of commensal microorganisms exist, known as the microbiota, which plays an important role in many biological functions including growth enhancement, nutrition, development, and metabolism ( 1 , 2 ). Recently, the microbiota has been found to be closely related to the host’s immune system, as it induces the occurrence of immune responses and enhances immune susceptibility ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teleosts have evolved both innate and adaptive immune systems to provide protection against pathogen invasion and tissue damage through a variety of defense responses including the induction of interferons (IFNs), inflammatory cytokines, chemokines, and the activation of cell death pathways [1][2][3]. The innate immunity has been demonstrated as the first line in the host immune defense, which is initiated by the recognition of pathogen-associated molecular patterns (PAMPs) or damage-associated molecular patterns (DAMPs) through a series of receptors termed pattern recognition receptors (PRRs) including toll-like receptors (TLRs), nucleotide-binding oligomerization domain (NOD)like receptors (NLRs), retinoic acid inducible gene I (RIG-I)-like receptors (RLRs), C-type lectin receptors (CLRs), and absent in melanoma 2 (AIM2)-like receptors (ALRs), which finally activate the host immune response through an interaction with the downstream signaling molecules [4,5].…”
Section: Introductionmentioning
confidence: 99%